POLA SPASIAL HARGA TANAH UNTUK PERENCANAAN STRATEGIS DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN (STUDI KASUS: KOTA BANDUNG, JAWA BARAT, INDONESIA) - Alfita Puspa Handayani; Albertus Deliar; Rizqi Abdulharis (Fakultas Seni Rupa dan Desain ITB, 2021)
Sustainable development goals are expected to be achieved by 2030. One of the goals of sustainable development is to build cities and settlements that are inclusive, safe, and resilient. Bandung as one of the cities with very rapid development growth during the last 10 years has experienced changes in land prices, which are also very fast. Land prices are proven to have a relationship with development in an area. The more complete public facilities, social facilities, and accesses in an area, the higher the price is. This study has determined the spatial pattern of land prices in Bandung using four spatial cluster analysis methods. It is found that the spatial pattern of land prices in Indonesia is clustered. The results of this spatial pattern can be used as the basis for strategic planning for Bandung, especially to serve areas that can still be developed into new development centers supported by environmental planning and sustainable development.